Flexicurity or Flexicarity? - A Portuguese Overview - Noémia Bessa Vilela; José Caramelo Gomes; Natacha Silva (LeXonomica, 2017)
Due to the increasing competition on the labour market, the search for new approaches to labour legislations led to the creation and adoption, in some countries, of so called “flexicurity”. “Flexicurity” became top of the list in the policy agenda in the European Union, but there is doubt that such an agenda for encompassing labour market reform providing not employment. As sources are used “flexicurity” models, in countries where it has already been successfully implemented, as well as Eurostat data, information made available by the European Commission, as well as doctrinal and research papers. Portuguese jurisdiction is considered by national legal doctrine as a closed model. Heavy regulation and constitutional constraints drive an almost unanimous rejection of the possibility to introduce the concept at national level. This article's goal is to discuss the ways the concept could be introduced in the Portuguese jurisdiction. Would the model effectively create security, or would it result in precarity?